2020
DOI: 10.5488/cmp.23.43708
|View full text |Cite
|
Sign up to set email alerts
|

Insights into nature of a magnetization plateau of 3d-4f coordination polymer [Dy2Cu2]n from a spin-1/2 Ising-Heisenberg orthogonal-dimer chain

Abstract: The ground state and magnetization process of an exactly solved spin-1/2 Ising-Heisenberg orthogonal-dimer chain with two different gyromagnetic factors of the Ising and Heisenberg spins are investigated in detail. It is shown that the investigated quantum spin chain exhibits up to seven possible ground states depending on a mutual interplay of the magnetic field, intra- and inter-dimer coupling constants. More specifically, the frustrated and modulated quantum antiferromagnetic phases are responsible in zero-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The investigations brought a deeper insight into the thermal and magnetic-field-driven changes of the phenomenon [36][37][38][39][40][41][42][43], the impact of the model's parameters on the phenomenon [36,[39][40][41][42][43][44][45], as well as the evolution of the phenomenon near and above second-order (continuous) phase transitions [44,45] without any artefacts arising from approximations. Despite their simplicity and the general opinion that the simpler mixed-spin Ising-Heisenberg systems involving isolated local quantum correlations are artificial models, some of the results were in a very good correspondence with ones obtained for more complex Heisenberg counterparts [40] and also with experiments [38,46,47].…”
Section: Introductionmentioning
confidence: 52%
“…The investigations brought a deeper insight into the thermal and magnetic-field-driven changes of the phenomenon [36][37][38][39][40][41][42][43], the impact of the model's parameters on the phenomenon [36,[39][40][41][42][43][44][45], as well as the evolution of the phenomenon near and above second-order (continuous) phase transitions [44,45] without any artefacts arising from approximations. Despite their simplicity and the general opinion that the simpler mixed-spin Ising-Heisenberg systems involving isolated local quantum correlations are artificial models, some of the results were in a very good correspondence with ones obtained for more complex Heisenberg counterparts [40] and also with experiments [38,46,47].…”
Section: Introductionmentioning
confidence: 52%
“…It is possible to do so because the Dy 3+ ions represent Kramers ions with the ground-state multiplet 6 H 15/2 which is a subject of strong crystal-field splitting into eight well separated Kramers doublets [33,34], even though two different types of the oximate O-N bridges are realized between Cu 2+ and Dy 3+ ions in the real [CuDy 2 Cu] cell [23]. Our recent study [30], providing a satisfactory theoretical fit of the magnetization data reported for [Dy 2 Cu 2 ] n at the temperature T = 0.5 K, is the convincing evidence for this. The magnetic structure of the corresponding spin-1/2 Ising-Heisenberg orthogonal-dimer chain, in which the Ising spins σ correspond to the Dy 3+ magnetic ions, the Heisenberg spins S correspond to the Cu 2+ magnetic ions.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper we build on findings in the recent article [30]. Taking into account the values of interaction coupling constants and gyromagnetic factors of spins fitted from magnetization data of [Dy 2 Cu 2 ] n , we theoretically examine a possible bipartite entanglement within Cu 2+ -Cu 2+ dimers in this polymer through the symmetric version of the isotropic spin-1/2 Ising-Heisenberg orthogonal-dimer chain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations